El equipo de investigación: un reto y una realidad - Alfaro Rodríguez, Magdalena; Gamboa Jiménez, Alejandra; Jiménez Sánchez, Susana; Martín Pérez, Jorge R.; Ramírez González, Andrea (Revista Electrónica Educare, 2010)
This paper presents the different initial challenges, work processes, team formation and learning content obtained by researchers of the interdisciplinary team of the project called Proyecto Perfiles, Dinámicas y Desafíos de la Educación Costarricense (Profiles, Dynamics and Challenges of the Costa Rican Education) of Centro de Investigación y Docencia en Educación (CIDE) (Research and Teaching Center), from Universidad Nacional, in its third phase. There will be an analysis showing how cooperative work and shared leadership as a team made a successful impact in the research process.